The political institutionality behind the government-police relation in the province of Buenos Aires (2015-2023) - Navarro Urquiza, Pablo (Revista del CLAD Reforma y Democracia, 2025)
The specialized literature on the political government of security and the police in the province of Buenos Aires, Argentina, indicates that the performance of recent government administrations has oscillated between reformist initiatives, aimed at modernizing the functioning of the security system and the police, and conservative or regressive initiatives, marked by the search to dismantle the guidelines promoted by other governments. However, little is known about the impact of these issues at the level of political institutionality. From the approach of organizational structures and security government, and through the application of a case study, this paper analyzes the political institutionality of the ministry of security of the province of Buenos Aires aimed at security and police government during the years 2015 and 2023, that is, during the administration of María Eugenia Vidal and Axel Kicillof at the head of the provincial governorship. The results of the research show which were the main axes that guided the management of both governors in the above-mentioned aspects. The work contributes to scientific inquiry and reflection on issues that are little addressed by the social sciences.